Atom tunnelling in the reaction NH3+ + H2 → NH4+ + H and its astrochemical relevance. (29th September 2016) - Álvarez-Barcia, Sonia; Russ, Marie-Sophie; Meisner, Jan; Kästner, Johannes
Abstract : The title reaction is involved in the formation of ammonia in the interstellar medium. We have calculated thermal rates including atom tunnelling using different rate theories. Canonical variational theory with microcanonically optimised multidimensional tunnelling was used for bimolecular rates, modelling the gas-phase reaction and also a surface-catalysed reaction of the Eley–Rideal type. Instanton theory provided unimolecular rates, which model the Langmuir–Hinshelwood type surface reaction. The potential energy was calculated on the CCSD(T)-F12 level of theory on the fly. We report thermal rates and H/D kinetic isotope effects. The latter have implications for observed H/D fractionation in molecular clouds. Tunnelling causes rate constants to be sufficient for the reaction to play a role in interstellar chemistry even at cryogenic temperature. We also discuss intricacies and limitations of the different tunnelling approximations to treat this reaction, including its pre-reactive minimum.